Pengaruh Motivasi Belajar dan Disiplin Belajar terhadap Hasil Belajar Ekonomi : The Effect of Learning Motivation and Learning Discipline on Economic Learning Outcomes - Faizin, Muhammad Ilham; Hermawan, Yoni; Srigustini, Astri (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The issue addressed in this study is the economic learning outcomes of students. This research aims to determine the influence of learning motivation and learning discipline on the learning outcomes of 10th and 11th-grade students at MAN 5 Tasikmalaya in the 2024/2025 academic year. This study employs a quantitative approach using a survey method. The population consists of 191 students, with a saturated sampling technique used. Data collection was conducted through the distribution of questionnaires. The data analysis techniques include tests for heteroscedasticity, multiple linear regression analysis, normality test, multicollinearity test, and hypothesis testing, utilizing SPSS 24 for Windows. The results of the study indicate that learning motivation has a negative and significant effect on learning outcomes. Learning discipline has a positive and significant effect on learning outcomes. Furthermore, peer environment, learning motivation, and learning discipline collectively have a significant influence on students’ learning outcomes.